2017
DOI: 10.1159/000477162
|View full text |Cite
|
Sign up to set email alerts
|

PD-1 Checkpoint Inhibitor Associated Autoimmune Encephalitis

Abstract: Objective: To report first-hand narrative experience of autoimmune encephalitis and to briefly review currently available evidence of autoimmune encephalitis in cancer patients treated with immune checkpoint inhibitors. Setting: A case study is presented on the management of a patient who developed autoimmune encephalitis during nivolumab monotherapy occurring after 28 weeks on anti-PD-1 monotherapy (nivolumab 3 mg/kg every 2 weeks) for non-small cell lung cancer. Results: No substantial improvement was observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
49
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 5 publications
2
49
0
2
Order By: Relevance
“…Brain MRI findings may reveal temporal lobe enhancement or other findings but may also be unremarkable, as in our patient. Symptoms may include headaches, confusion, fevers, and focal neurologic deficits (including aphasia and ataxia) . This case was notable in that the neurologic symptoms occurred after an episode of epididymo‐orchitis.…”
Section: Discussionmentioning
confidence: 92%
“…Brain MRI findings may reveal temporal lobe enhancement or other findings but may also be unremarkable, as in our patient. Symptoms may include headaches, confusion, fevers, and focal neurologic deficits (including aphasia and ataxia) . This case was notable in that the neurologic symptoms occurred after an episode of epididymo‐orchitis.…”
Section: Discussionmentioning
confidence: 92%
“…11 Acute encephalopathy from demyelination is rarely discussed. 9,12 A meta-analysis published in 2017 discussed the common neurotoxic adverse effects of nivolumab, which included fatigue, headache, dysgeusia (distortion of the sense of taste), vertigo, paresthesia, anxiety or malaise, and peripheral neuropathy. The study concluded that nivolumab treatment is associated with decreased risk of paresthesia and peripheral neuropathy when compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that ours is the second case in the literature where nivolumab as monotherapy was given, and the patient experienced AIE as a part of severe immune-related adverse events. 9 Schneider et al 9 first reported acute AIE in a patient taking nivolumab for non-small cell lung cancer. Within 24 hours after administration of methylprednisolone (1.33 mg/kg body weight), the patient's Glasgow Coma Score improved from 7 at the time of presentation to 15.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This mechanism was successfully translated into medicine that boosts immune responses against tumor cells, one of the most important breakthroughs in cancer treatment and a complementary approach to direct targeting of tumor cells [25]. Notably, autoimmune diseases occur in a number of patients who undergo treatment with immune checkpoint inhibitors, including affection of the gastrointestinal tract with diarrhea as well as severe systemic immunopathology with fatal course [26][27][28][29][30][31][32][33][34][35]. These observations underline the importance of immune checkpoints in balancing immune responses and demonstrate the power of these molecular brakes of the immune system during ongoing immune responses.…”
Section: Introductionmentioning
confidence: 99%